Bangladesh country brief - Akhtar, Nazneen; Yosef, Sivan; Nisbett, Nicholas (Transform Nutrition, 2016)
There have been remarkable improvements in welfare and human development in Bangladesh in recent years. These have been supported by rapid economic growth and many successful social and health programmes undertaken by the government and non-governmental organisations, shrinking family sizes and growing access of women to education. Overall improvements in child nutrition measured in terms of reduced child stunting can be seen as part of this success story, though there are still many areas of nutrition in significant need of attentio